Research hotspots and trends on illicit drugs: a bibliometric and visualized analysis - Chen, Yinyu; Zheng, Gaolin; Yang, Xinyan; Wu, Guangmei; Nie, Qianyun; Zhang, Peng (Frontiers in Medicine, 2025)
ObjectiveTo explore the current status and developmental trend of drug research in the international arena through bibliometric methods and visualization analysis.MethodsIn this study, drug-related articles published from 2015 to 2024 in the core collection of Web of Science databases were analyzed, and bibliometric and visualization analyses of annual publication volume, countries (regions), institutions, journals, and keywords were achieved using CiteSpace v.6.2.R7 software.ResultsA total of 5,797 publications on drug research were included between 2015 and 2024, with the annual publication volume progressively increasing on an annual basis. Among the 117 publishing countries (regions), the United States published the most articles, with 1,534 publications, followed by the United Kingdom with 611 articles. Additionally, the literature was sourced from 1,441 journals, with a total of 1,398 publications in the top 10 journals. DRUG TESTING AND ANALYSIS ranked first with 259 articles. Finally, keyword clustering and emergence analysis revealed that current research hotspots were concentrated in the areas of drug abuse, new psychoactive substances, synthetic drugs, and wastewater treatment.ConclusionThe volume of drug-related research publications is steadily increasing globally. However, there is a pressing need to further strengthen global collaboration and interdisciplinary research, as well as to promote the development of a broader international scientific research network. In particular, advanced technological approaches and policy strategies must be explored to address the global challenges posed by drug-related issues, particularly in the detection, management, and prevention of synthetic drugs. The enhancement of data sharing, technological exchange, and collaborative actions among nations plays an instrumental role in the establishment of a more efficient and coordinated global drug governance system, better equipping the international community to address the threats posed by drugs to public health and social security.